2022
DOI: 10.3390/diagnostics12102427
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Added Value of SARS-CoV-2 Antigen Detection in Blood Samples

Abstract: This study evaluated the performances of immunoassays (LFIA and ELISA) designed for SARS-CoV-2 Antigen (Ag)-detection in nasopharyngeal (NP) and serum samples in comparison to RT-PCR. NP samples from patients with respiratory symptoms (183 RT-PCR-positive and 74 RT-PCR-negative samples) were collected from March to April and November to December 2020. Seroconversion and antigen dynamics were assessed by symptom onset and day of RT-PCR diagnosis. Serum samples from 87 COVID-19 patients were used to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that SARS-CoV-2 N-Ag can be detected in the blood (including serum and plasma samples) of COVID-19 patients ( Ogata et al, 2020 ; Ahava et al, 2022 ; Su et al, 2021 ; Thudium et al, 2021 ; Olea et al, 2021 ). SARS-CoV-2 N-Ag detection in the blood not only provides a new diagnostic biomarker for COVID-19 but also contributes to identifying the relationship with disease severity ( Zhang et al, 2021 ; Li et al, 2020 ; Hingrat et al, 2020 ; Oueslati et al, 2022 ). Therefore, it is still of clinical significance to explore the diagnostic value and characteristics of serum N-Ag in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that SARS-CoV-2 N-Ag can be detected in the blood (including serum and plasma samples) of COVID-19 patients ( Ogata et al, 2020 ; Ahava et al, 2022 ; Su et al, 2021 ; Thudium et al, 2021 ; Olea et al, 2021 ). SARS-CoV-2 N-Ag detection in the blood not only provides a new diagnostic biomarker for COVID-19 but also contributes to identifying the relationship with disease severity ( Zhang et al, 2021 ; Li et al, 2020 ; Hingrat et al, 2020 ; Oueslati et al, 2022 ). Therefore, it is still of clinical significance to explore the diagnostic value and characteristics of serum N-Ag in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is growing evidence that the detection of viral proteins in the blood may represent a new approach to improve the screening or diagnosis of SARS-CoV-2 infection ( Mathur et al, 2022 ; Verkerke et al, 2022 ; Wang et al, 2021 ; Zhang et al, 2021 ; Li et al, 2020 ; Hingrat et al, 2020 ). Previous studies have also reported that decreased nucleocapsid antigen (N-Ag) levels in the blood were significantly associated with increased anti-SARS-CoV-2 antibodies ( Zhang et al, 2021 ; Shan et al, 2021 ; Costa et al, 2022 ; Oueslati et al, 2022 ). In addition, several studies have shown that N-Ag levels in the blood are closely correlated with disease severity, as reflected by intensive care unit (ICU) admission and grade of disease severity in COVID-19 patients ( Wang et al, 2021 ; Zhang et al, 2021 ; Oueslati et al, 2022 ; Favresse et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, several issues should be taken into consideration and reassessed appropriately. First and foremost, it must be highlighted, that, according to the molecular biology principles, «molecular tests», include all nucleic acid amplification tests (NAATs) such as the widely performed polymerase chain reaction (PCR) assay for the genetic identification of SARS-CoV-2 and all serological tests, either for antigen or antibody detection, such as the lateral flow immunoassays (LFIAs) that society regarded as ‘rapid tests’, as well as the laboratory antigen and antibody detection tests, such as the widely preferred enzyme-linked immunosorbent assay (ELISA) [ 21 , 22 , 23 , 24 , 25 ]. All these testing platforms and several others have already been applied for managing the molecular diagnosis of infectious diseases, while common and new ones were applied for the identification of SARS-CoV-2 [ 26 ].…”
Section: Current Covid-19 Pandemic-derived Molecular Diagnostics’ Fac...mentioning
confidence: 99%
“…Other stricter community measures were the so-called «lockdowns» that limited activities or access to resources, facilities, or institutions, leading to generalized home isolation [ 10 , 11 , 12 ]. Moreover, a plethora of diagnostic tests and community mass-testing strategies were evident, in parallel with various vaccination platforms initially authorized for emergency use, and the so-called «COVID-19 vaccination certificate/pass», SARS-CoV-2 infection certificate/pass, or the SARS-CoV-2 negative molecular diagnostic test certificate/pass in some countries [ 2 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%